EFEKTIVITAS PENGGUNAAN QUICK RESPONSE CODE INDONESIAN STANDARD (QRIS) SEBAGAI METODE PEMBAYARAN NONTUNAI BUS TRANS MAMMINASATA (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2025)
The aim of this research is to determine the effectiveness of using the Quick Response CodeIndonesian Standard (QRIS) as a non-cash payment method on the Trans Mamminasata Bus inMakassar City. This research uses qualitative methods, with a qualitative descriptive researchtype where data collection techniques are carried out through observation, interviews anddocumentation. The research results show that (a) the accuracy of the program targets showsthat the use of QRIS is still less effective in targeting the general public and all users of TemanBus services. (b) socialization of the program, showing that it is almost effective because it isnot only carried out directly. (c) program objectives, indicating that payments via theIndonesian Standard Quick Response Code (QRIS) aim to make it easier for passengers. (d)program monitoring, showing that the monitoring carried out is almost effective but there arestill many people who do not know whether there is monitoring carried out by parties related toFriends of the Bus.